PERANCANGAN MEDIA INTERAKTIF BERBASIS MASKOT DAN INFOGRAFISSEBAGAI MEDIA KAMPANYE SOSIAL UNTUK MENINGKATKAN KEPEDULIAN MASYARAKAT DALAM MEMILAH SAMPAH DI AREA WISATA TAWANGMANGU - Muntjar, Datan Grahito; Haryatno, Yulius Rudi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to design infographic and mascot as social campaign media to increase public awareness of the environment in the Grojogan Sewu tourist area, Tawangmangu. This design departs from the reality of waste distribution around the main destination area of ​​Grojogan Sewu. This shows that the level of public concern for protecting the area from the spread of waste is still low. Designing mascot and infographic are seen as a solution to increase awareness of local communities and tourists. This design research uses the design thinking method. Data collection was carried out through observation. This design research resulted in an infographic and mascot